Targeted microbial control for hydrocarbon reservoir: Identify new biocide offerings for souring control using thermophile testing capabilities. (January 2018) - Yin, Bei; Williams, Terry; Koehler, Thomas; Morris, Brandon; Manna, Kathleen
Abstract: Mesophilic and thermophilic sulfide-producing microorganisms can thrive in underground environments and cause hydrocarbon reservoir souring during energy recovery operations, and the temperature regime underground can affect the efficacy of biological control programs. In this study, we evaluated the efficacy of selected biocides using a thermophilic and a mesophilic sulfide-producing bacteria. A commonly used oilfield biocide, glutaraldehyde (Glut), and three non-traditional oil&gas field biocides, cis-1-(3-chloroallyl)-3, 5, 7-triaza-1-azoniaadamantane chloride (CTAC), 4, 4-dimethyloxazolidine (DMO), and tris (hydroxymethyl) nitromethane (THNM), were used for the investigation. It was found that Glut was very effective against both mesophilic and thermophilic sulfide-producing bacteria. However, its efficacy persisted for shorter periods at 75° C compared to 35° C. Higher doses of Glut were required for complete bacterial kill over an extended period of time. As traditional preservative biocides, CTAC, DMO and THNM acted slower as compared to Glut. However, their efficacy was enhanced at elevated temperature. CTAC, DMO and THNM all showed improved performance at 75° C versus 35° C, and their efficacy persisted longer than Glut. This study highlights the potential of non-traditional oil&gas field biocides for microbial and souring control in reservoirs with challenging temperature conditions. Highlights: Glut was effective against both meso- and thermophilic sulfide-producing bacteria. Efficacy of CTAC, DMO and THNM persisted longer than Glut at 75 °C. CTAC, DMO and THNM have good potential for extended reservoir protection.